Prediction of live birth in vitrified-warmed 1PN-derived blastocyst transfer: Overall quality grade, ICM, TE, and expansion degree - Wang, Tiantian; Si, Jiqiang; Wang, Bian; Yin, Mingru; Yu, Weina; Jin, Wei; Lyu, Qifeng; Long, Hui (Frontiers in Physiology, 2022)
Background: Numerous studies have reported transfer of blastocysts derived from monopronuclear (1PN) zygotes achieved live births. However, the potential value of morphology grading for prediction of 1PN blastocysts viability is unclear and the blastocyst selection criterion for successful pregnancy has not been set up yet. To assess ability of blastocyst morphology grading system based on three parameters, inner cell mass (ICM) and trophectoderm (TE), and expansion degree, to predict outcomes of a cycle with single 1 PN blastocyst transfer. Methods: A total of 266 frozen thawed 1PN embryo transfer (FET) cycles for IVF treatment at the Shanghai Ninth People’s Hospital between 20** and 20** were included. Electronic records of patients were retrospectively analyzed. The basal characteristics, embryo grading as well as clinical outcomes were compared between the two groups. The association of morphology parameters with pregnancies and live births was analyzed. Logistic regression was adopted to set up a prediction model of live births. Results: Transfer of the good quality blastocyst achieved significant higher pregnancies (biochemical pregnancy: 59%; clinical pregnancy: 56.4%) and live birth (48.7%) than those in the group of the medium (biochemical pregnancy: 59%; clinical pregnancy: 49.6%; live birth: 40.4%) or poor-quality (biochemical pregnancy: 38.4%; clinical pregnancy: 34.9%; live birth: 26.7%) blastocysts (P<0.05). There was a significant association between ICM and live birth. A prediction model of live births involving ICM, TE and expansion degree was set up. Conclusion (s): In 1PN transfer cycles, a higher overall blastocyst quality is shown to correlate most strongly with optimal pregnancy and live birth outcomes. Selection of high quality blastocysts for transfer should consider first the ICM score. The prediction model of live births based on ICM, TE and expansion degree, may help predict successful pregnancy in 1PN single-blastocyst transfer cycles.